Hypobaric hypoxia causes impairment of spermatogenesis in developing rats at pre‐puberty. (27th February 2018) - Bai, Gang; Yang, Bin; Tong, Weimin; Li, Hongjun
Summary: The effect of hypoxia on the spermatogenesis of male Wistar rats ( n  = 32) at pre‐puberty was studied using a hypobaric chamber simulating an altitude of 5, 000 metres above sea level. Persistent hypoxic exposure with brief interruption for 3 weeks caused significant decreases in body and testis weights and testosterone level compared to the normobaric controls. Histologically, spermatogenic development was arrested; arrays of spermatids were misshaped; numbers of spermatogonia, Sertoli and Leydig cells were reduced; and apoptotic spermatocytes were increased substantially in the germinal epithelium of testis in the hypoxic‐exposed group. These hormonal and histopathological changes did not improve remarkably after 3 weeks of normobaric conditions. There was a significant decrease in sperm production when the rats in the hypoxia/oxygen‐resuming group were examined at 63 days of post‐natal age. Exposing rats to hypoxic conditions at pre‐puberty induced damages on spermatogenesis, which could affect sperm production after sex mature.